Fabrication and mechanical properties of three-dimensional enhanced TiAl/GH3536 hetero-honeycomb sandwich structure - Y. Luo; S.P. Hu; Y.Z. Liu; Y.X. Wang; X.G. Song; J. Cao (Journal of Materials Research and Technology, 2023)
The mechanical properties of honeycomb sandwich structures are improved using topological-reinforcement and material-strengthening. This study introduces a novel type of TiAl/GH3536 hetero-honeycomb sandwich structure, called the enhanced honeycomb sandwich structure, which boasts a relative density of core range of 3.2%–21.2%. The enhanced honeycomb sandwich structure is designed and fabricated through a vacuum-brazing method using BNi-2 brazing filler metal. The microstructure and out-of-plane compression behavior of both the as-brazed and original honeycomb cores are experimentally and analytically investigated. The study establishes good correlations between analytical predictions and experimental results. The results highlight the sensitivity of the mechanical properties of the enhanced honeycomb cores to the unit-cell size and parent–alloy properties, specifically inelastic buckling, and elastic modulus. The compressive characteristics of the enhanced honeycomb sandwich structures were thoroughly examined, and it was determined that the efficient filling of gaps between the honeycomb core walls with liquid BNi-2 brazing filler metal, coupled with the optimal core structure, resulted in the precipitation of mesh-like Mo-boride compounds within the GH3536 parent material. This resulted in a significant increase in the compressive strength and elastic modulus, by up to 57.4% and 26.3%, respectively. The combination of topological-reinforcement and material-strengthening provided a way to achieve lightweight sandwich structures with high specific strengths and low densities, which is important on the fabrication of engineering bioinspired materials and devices designed based on honeycomb structures.